Trade in services and gender: the case of Chile - Antonieta Sepúlveda Carreras (Latin American Journal of Trade Policy, 2024)
In recent decades, the relationship between international trade and gender has gainedrelevance, although the trade in services from a gender perspective remains underexplored.Chile, one of the most globally integrated economies, faces the challenge of diversifying itsexport basket, which is highly concentrated in commodities, and reducing persistent gendergaps in its economy. The services sector, employing a large proportion of women,represents a strategic opportunity to address both challenges. This study analyzes therelationship between gender and trade in services in Chile, using an exploratory qualitativeapproach that serves as a reference for future research and as input for the design of publicpolicies. The findings highlight the importance of designing specific public policies topromote female participation in service exports and contribute to more inclusive andsustainable economic development.